hUC-MSC preserves erectile function by restoring mitochondrial mass of penile smooth muscle cells in a rat model of cavernous nerve injury via SIRT1/PGC-1a/TFAM signaling - Mengbo Yang; Xinda Chen; Ming Zhang; Xiaolin Zhang; Dongdong Xiao; Huiming Xu; Mujun Lu (Biological Research)
Abstract Background Cavernous nerve injury-induced erectile dysfunction (CNI-ED) is a common complication following radical prostatectomy and severely affects patients’ quality of life. The mitochondrial impairment in corpus cavernosum smooth muscle cells (CCSMCs) may be an important pathological mechanism of CNI-ED. Previous studies have shown that transplantation of human adipose derived stem cells (ADSC) can alleviate CNI-ED in a rat model. However, little is known about the effect of human umbilical cord mesenchymal stem cells (hUC-MSC) on CNI-ED. It remains unclear whether hUC-MSC can ameliorate mitochondrial damage in CCSMCs. In this study, we aimed to investigate the impacts of hUC-MSC on the mitochondrial mass and function of CCSMCs, as well as elucidate its underlying molecular mechanism. Methods The CNI-ED rat model was established by bilaterally crushing cavernous nerves. Subsequently, hUC-MSC were transplanted into the cavernosum and ADSC were injected as a positive control group. Erectile function evaluation and histological detection were performed 4 weeks after cell transplantation. In vitro, CCSMCs underwent hypoxia and were then co-cultured with ADSC or hUC-MSC using a transwell system. The mitochondrial mass and function, as well as signaling pathways, were investigated. To explore the role of the SIRT1/PGC-1α/TFAM pathway in regulating mitochondrial biogenesis of CCSMCs, we knocked down SIRT1 by siRNA. Results The administration of hUC-MSC significantly improved erectile function of CNI-ED rats and reduced the ratio of collagen to smooth muscle. Specifically, hUC-MSC treatment restored mitochondrial mass and function in CCSMCs injured by CNI or hypoxia, and inhibited the apoptosis of CCSMCs. Mechanistically, the application of hUC-MSC activated SIRT1/PGC-1α/TFAM pathway both in rat penile tissues and CCSMCs. In addition, knockdown of SIRT1 in CCSMCs abolished the protective effects of hUC-MSC on mitochondrial mass and function, while leading to an increase in cellular apoptosis. Conclusions hUC-MSC contribute to the recovery of erectile function in CNI-ED rats by restoring mitochondrial mass and function of CCSMCs through the SIRT1/PGC-1α/TFAM pathway. Our present study offers new insights into the role and molecular mechanisms of hUC-MSC in regulating mitochondrial homeostasis, thereby facilitating the restoration of the erectile function in CNI-ED.